Comparison and Analysis of Calculation Methods for Rated Static Load of Planetary Roller Screw Mechanism - Kang Xinhong; Wei Peitang; Hu Rui; Zhou Pengliang; Du Xuesong; Zhu Caichao (Jixie chuandong, 2022)
Planetary roller screw mechanism (PRSM) is a new type of heavy duty transmission devices. Rated static load is a key indicator to reflect its carrying capacity. Aiming at the problems of inconsistent calculation methods of PRSM rated static load and large difference between calculation results at present, four calculation methods of PRSM rated static load based on ball screw, rolling bearings, yield limit and elastic-plastic linear strengthening are expounded and corresponding calculation models are established; the PRSM elastic-plastic finite element contact analysis model is established, and the accuracy of the four calculation methods is compared and verified; an improved PRSM rated static load calculation method based on rolling bearing standards is proposed. The results show that the calculated results of the rated static load based on rolling bearings agree well with the finite element results. The improved calculation method reduces the average error from 17.03% to 8.90%, which can accurately calculate the rated static load of PRSM. It provides theoretical support for the design and selection of planetary roller screw mechanism.